Design and Development of a Hydroponic Growing Media Monitoring System for The Growth of Melon Plants from Flowering to Harvest Based on The Internet of Things (IoT): Case Study: Lara’s Melon Hydroponic, Pasir Kulon, Karanglewas District, Banyumas - Danang Dasa; Aulia Desy Nur Utomo (Jurnal E-Komtek, 2026)
Hydroponic melon (Cucumis melo L.) cultivation requires precise environmental parameter monitoring to achieve optimal results. This study aims to design an Internet of Things (IoT)-based monitoring system to monitor temperature, humidity, pH, and TDS in real-time via a website. The system was developed using the Prototype method with Arduino Uno and NodeMCU ESP8266 as the main controllers. The testing phase included system functionality testing, sensor calibration, and User Acceptance Testing (UAT). Technical testing results showed that the average accuracy of the DHT11 temperature sensor reached 96.61%, the pH sensor 99.67%, and the TDS sensor 64.67%. Meanwhile, the UAT results indicated a system feasibility level of 89.33%, categorized as "Very Feasible." System implementation over 8 weeks demonstrated an improvement in harvest quality, where monitored plants had an average fruit weight of 1.398 kg and a sweetness level of 13.25 °Brix, outperforming unmonitored plants which recorded an average of 1.379 kg and 12.75 °Brix. In conclusion, this system effectively provides measurable data, is feasible for user implementation, and contributes to improving harvest quality.